Three rare and enigmatic South American skinks - Miralles, Aurélien; Chaparro, Juan Carlos; Harvey, Michael B. (Zootaxa, 2009)
Three enigmatic skinks, Mabuya nigropalmata Andersson, 1918, Tiliqua maculata Gray, 1839, and Trachylepis (Xystrolepis) punctata, Tschudi, 1845, have been reported from widely separated localities on the South American mainland. They remain the three rarest and most poorly known South American skinks and were known only from type material until recently. In this paper, we comment on recent rediscoveries of M. nigropalmata in the western Amazon of Peru and Bolivia. Using cytochrome b and 12S DNA sequences, we resolve this species’s phylogenetic position within Mabuya sensu stricto and demonstrate its specific distinctiveness, especially from the superficially similar species M. frenata. In addition, we show that neither Trachylepis (Xystrolepis) punctata nor Tiliqua maculata can be placed within Mabuya. A suite of morphological characteristics requires the transfer of these two species to the mostly Afro-Malagasy genus Trachylepis. To correct the secondary homonymy of Tschudi’s name, we propose a replacement name for T. punctata. We designate NRM 23258A as the lectotype of Mabuya nigropalmata Andersson and MNHN 2932 as the lectotype of Trachylepis maculata (Gray) new combination. Finally, we propose an identification key to Mabuya of the Amazon basin and adjacent regions.